A Survey on Business Profitability for a Music Artist by Advertising on YouTube - KUMAR, SUMIT; JAIN, VIPIN (The journal of contemporary issues in business and government, 2021)
In present times, youth and elders are focusing on refining their talents with the advancement of technology more artists are getting encouraged to pursue their career in music industry, along with having the talent in the artist, it is required to strategically market these skills. It has been observed that with step-by-step marketing of an artist’s talent via a digital marketing platform and then investing money in launching that artist gives better results. It is also observed that YouTube plays a significant role when opted as a means of digital marketing, thus, the current survey finds that YouTube works as a potential medium in promoting the talent and results in an increased number of fans of a new artist. Thus, current study opens the future perspective to conduct more research in the connection of different social media platform and marketing strategy.